PERANCANGAN VIDEO ANIMASI LIRIK LAGU SAYU - Puspita, Ako Naomi Ratna; Haryatno, Yulius Rudi (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
Lyric videos play an important role in the music industry, combining visual, audio and text elements to convey the message of a song. This research aims to animate the lyric video for the song